Respostas hidrossedimentológicas em ambientes com diferentes níveis de conservação - Chaparro, Fosco Emmanuel Gugliotta Ruggeri (2024)
The research conducted in the Experimental Basin of the Curu Valley, Ceará, aimed to analyze ephemeral Watersheds in the Caatinga, a semi-arid region known for its extensive biodiversity but paradoxically subjected to intense degradation due to human activity. Focusing on soil conservation, the study covered four distinct areas, varying in terms of vegetation cover and management practices. The methodology employed included the installation of structures such as rain gauges, Class A tanks, and automatic sensors. Erosion plots were established for monitoring, allowing the assessment of different areas: Dense Caatinga (46 years of conservation), Sparse Caatinga (15 years), Herbaceous Cover (1 year), and Exposed Soil (no cover after 3 years of family farming). Over seven months, 57 rainfall events were monitored, revealing a concentrated distribution in the months of March and April. The total precipitation exceeded the regional average by 4.4%. Erosivity analysis indicated the significant influence of rainfall events with volumes exceeding 20 mm on the occurrence of water erosion. The results highlighted the direct relationship between soil cover and runoff volume, underscoring the crucial importance of vegetation in mitigating erosion. Dense Caatinga, with 46 years of conservation, proved more effective in reducing runoff, soil loss, and nutrient loss compared to cultivated areas. The methodology of sample collection, laboratory analysis, and measurement of physicochemical parameters contributed to understanding the interaction between response processes, erosion, runoff, and soil cover conservation. Statistical analysis, including Principal Component Analysis, was employed to interpret the association between variables. In summary, the study not only provides important insights into the dynamics of soil erosion and nutrient loss in the Caatinga but also highlights the effectiveness of conservation practices over time, based on a robust methodology incorporating various monitoring and analysis techniques